PENGARUH PERAN GURU TERHADAP MOTIVASI BELAJAR SISWA PADA MATA PELAJARAN BAHASA INDONESIA DI KELAS III MI NAHDLATUL MUBTADIIN - Nabil Al Mutasemi; Abdussalam (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
Learning motivation plays a crucial role in improving academic achievement by instilling moral, ethical, and cultural values. Indonesian language learning not only develops effective skills but also deepens cultural understanding and enhances literacy. This research aims to evaluate the influence of teacher roles on student learning motivation in grade III of MI Nahdlatul Mubtadiin using the One Group Pretest-Posttest Design experimental method. Teacher roles are considered vital in education, particularly in Indonesian language teaching; the absence of teacher intervention can reduce student motivation. The results of the Paired Sample T-Test hypothesis testing show statistical significance (p < 0.05), confirming the significant influence of teacher roles on student motivation. The increase in student learning outcomes from a pretest score of 16.00 to a posttest score of 37.00 confirms the significant impact of teacher roles at MI Nahdatul Mubtadiin.